High-Q plasmonic graphene absorbers for electrical switching and optical detection. (30th September 2020) - Liu, Zhengqi; Zhou, Jin; Liu, Xiaoshan; Fu, Guolan; Liu, Guiqiang; Tang, Chaojun; Chen, Jing
Abstract: In this work, we report an intensive theoretical study on the achieving of multiple ultra-sharp and near-unity absorption in a cavity enabled graphene absorber. The plasmonic-induced magnetic resonance, i.e., magnetic plasmon is excited and localized efficiently via the one-dimensional metallic oblique slit array. The slit concentrates highly for the plasmonic field in a limited spatial cavity and simultaneously intensifies the graphene-field coupling, which leads to the emergency of the multi-band high-quality ( Q ) factor (190) ultra-sharp perfect absorption. Although the graphene-slit interaction area is just 17.7% of the structural size, the maximal absorption efficiency reaches 99.8%. In the near-infrared range, a large spectral intensity change of 82% is achieved when the graphene's Fermi energy is manipulated by a slight value of 0.03 eV, which directly introduces a viewable switching process between the operation "on" and "off" states. The optical sensing sensitivity is also up to 1276 nm/RIU and the FOM factor reaches 106. During the application for temperature detecting, the resolution limit can be as down as 3 × 10 −3  °C (K), suggesting a desirable temperature detector. Moreover, polarization-adjustable and angle-insensitive properties for the plasmonic graphene absorber could further promote enormous applications for the active optoelectronic devices. Graphical abstract: Image 1 Highlights: A high- Q plasmonic graphene absorber is demonstrated via an oblique air slit array in the metal substrate. A viewable switching process between the operation "on" and "off" states is demonstrated. High-performance optical sensor and temperature detector are obtained via this graphene absorber.